Origin and primary dispersal of the Mycobacterium tuberculosis Beijing genotype: Clues from human phylogeography - Mokrousov, Igor; Ly, Ho Minh; Otten, Tatiana; Lan, Nguyen Ngoc; Vyshnevskyi, Boris; Hoffner, Sven; Narvskaya, Olga

(untitled) (Genome Research, 2005)
We suggest that the evolution of the population structure of microbial pathogens is influenced by that of modern humans. Consequently, the timing of hallmark changes in bacterial genomes within the last 100,000 yr may be attempted by comparison with relevant human migrations. Here, we used a lineage within Mycobacterium tuberculosis, a Beijing genotype, as a model and compared its phylogeography with human demography and Y chromosome-based phylogeography. We hypothesize that two key events shaped the early history of the Beijing genotype: (1) its Upper Palaeolithic origin in the Homo sapiens sapiens K-M9 cluster in Central Asia, and (2) primary Neolithic dispersal of the secondary Beijing NTF::IS6110 lineage by Proto-Sino-Tibetan farmers within east Asia (human O-M214/M122 haplogroup). The independent introductions of the Beijing strains from east Asia to northern Eurasia and South Africa were likely historically recent, whereas their differential dissemination within these areas has been influenced by demographic and climatic factors.